Konsep Manajemen Perubahan SDM Berbasis Reward Point Dalam Meningkatkan Kinerja Tenaga Pendidik dan Tenaga Kependidikan - Hosen, Hosen (Al-Abshar: Journal of Islamic Education Management, 2024)
In the concept of education, rewards are a tool to increase a person's interest and work enthusiasm. This method can associate a person's actions and behavior with feelings of happiness, enjoyment and will usually make them do a good job or deed repeatedly. Management of changes in human resources can be carried out through reward points as a supporting factor in improving the performance of human resources in an educational institution, especially teaching staff and educational staff. The purpose of this writing is to provide an explanation of the importance of human resource change management which can be carried out through reward points as one of the supporting factors in improving the performance of human resources in an educational institution. This research uses library research, which is a preparation by collecting, writing, editing and classifying, and making data and information relevant. This data and information was obtained from various written sources from various scientific books, drafting reports, scientific essays, theses and accompanying documents, regulations, encyclopedias, and written sources both printed and electronic and others. The conclusion of the research is that in order to be able to create human resources in the form of qualified teaching staff and education staff and continually improve their performance, one strategy that can be carried out by school principals is to provide rewards or reward points as appreciation and support for the achievements achieved by the staff. educators and educational staff so as to make schools of higher quality, more in demand and able to progress and develop following changing times. Because the process of developing human resources in an educational institution must also be based on needs analysis and very thorough planning, so that it can support the process of achieving the goals of the educational institution.